Sustainable water treatment: Fruit waste-derived ethanol extract for SiO₂ surface modification and enhanced methylene blue adsorption - Rasim Omanović; Amira Čopra-Janićijević; Sabina Begić; Maja Đekić; Jasmina Sulejmanović (Desalination and Water Treatment)
The uncontrolled and irrational discharge of pollutants from various industrial plants triggers environmental pollution, particularly affecting water resources, which are among the most endangered. Therefore, this study specifically focuses on the removal of methylene blue (MB) dye using the SiO2-G-70 %-RT adsorbent. The new adsorbent was prepared by modifying previously activated SiO₂ with ethanol extract derived from grapefruit peel. The successful modification was confirmed through a series of analyses, including FTIR, SEM, EDS and XRD. The uni-variant batch method, optimized for key adsorption parameters, revealed the optimal conditions: initial MB concentration (20 mg/L), pH (5−7), adsorbent mass (25 mg), contact time (40 min), and solution temperature (20 ± 2 °C). The sorption kinetics and isotherm models indicate that the adsorption mechanism occurs in a mixed mode. Based on calculated values for specific error parameters, such as the correlation coefficient (R2) and statistical functions: Chi-square test (χ2), normalized deviation (ND) and normalized standard deviation (NSD)), the pseudo-second-order and Freundlich isotherm models best describe the MB adsorption process using the SiO2-G-70 %-RT adsorbent. The results demonstrate the effective reuse of the adsorbent for at least four cycles, with a maximum adsorption capacity of 50.6 mg/g. The cost for the uptake of 1 g MB is 2.34$.